COVID-19 Vaccine Hesitancy in the LGBTQ+ Population: A Systematic Review - Ishan Garg; Hamza Hanif; Nismat Javed; Ramsha Abbas; Samir Mirza; Muhammad Ali Javaid; Suman Pal; Rahul Shekhar; Abu Baker Sheikh (MDPI AG, 2021)
The coronavirus 2019 (COVID-19) pandemic has disproportionately impacted lesbian, gay, bisexual, transgender, queer (LGBTQ+) people. Despite developing safe and effective COVID-19 vaccines, LGBTQ+ communities still faces challenges due to inequitable access and vaccine hesitancy. Vaccine hesitancy is a delay in the acceptance or refusal of vaccines despite the availability of vaccination services. Various studies have explored and tried to address factors influencing vaccine hesitancy. However, the LGBTQ+ population remains under- and misrepresented in many of these studies. According to the few studies that have focused on the LGBTQ+ population, several factors influencing vaccine hesitancy have been identified, with the most common factors in studies being concern about vaccine safety, vaccine efficacy, and history of bad experiences with healthcare providers. In order to rebuild the confidence of LGBTQ+ people in vaccines, governments, healthcare policymakers, and healthcare providers need to start by acknowledging, and then resolving, these disparities; building trust; dismantling systemic suppression and discrimination; and prioritizing the inclusion of LGBTQ+ people in research studies and public health policies.